The Lazarus Escherichia coli Effect: Recovery of Productivity on Glycerol/Lactose Mixed Feed in Continuous Biomanufacturing - Kittler, Stefan; Kopp, Julian; Veelenturf, Patrick Gwen; Spadiut, Oliver; Delvigne, Frank; Herwig, Christoph; Slouka, Christoph (Frontiers in Bioengineering and Biotechnology, 2020)
Continuous cultivation with E. coli has several benefits compared to classical fed-batch cultivation. The economic benefits would be a stable process, which leads to time independent quality of the product, and hence ease the downstream process. However, continuous biomanufacturing with E. coli is known to exhibit a drop of productivity after about four to five days of cultivation depending on dilution rate. These cultivations are generally performed on glucose, being the favorite carbon source for E. coli and used in combination with IPTG for induction. In recent works harsh induction with IPTG was changed to softer induction using lactose for the T7-based plasmids, with the result of reducing the metabolic stress and tunability of productivity. These mixed feed systems based on glucose and lactose result in high amounts of correctly folded protein. In this study we used different mixed feed systems with glucose/lactose and glycerol/lactose to investigate productivity of E. coli based chemostats. We tested three strains producing different model proteins, with the final aim of a stable long-time protein expression. While glucose fed chemostats showed the well-known drop in productivity after a certain process time, glycerol fed cultivations recovered productivity after about 200 h of induction, which corresponds to around 30 generation times. We want to further highlight that also the cellular response upon galactose utilization in BL21 might be a key parameter in process design to achieve stable productivity soon. This “Lazarus” phenomenon has not been described in literature before and may enable a stabilization of continuous cultivation with E. coli using different carbon sources.